1994
DOI: 10.1002/jemt.1070280605
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine 5′‐triphosphate promotes mineralization in differentiating chick limb‐bud mesenchymal cell cultures

Abstract: When chick limb-bud mesenchymal cells are plated in micromass culture, they differentiate to form a mineralizable cartilage matrix. Previous studies have demonstrated that, when the total inorganic phosphate concentration of the medium is adjusted to 3-4 mM by adding inorganic phosphate to the basal medium, the mineralized matrix formed resembles that of chick calcified cartilage in ovo. When the high-energy phosphates adenosine 5'-triphosphate (ATP) or creatine phosphate are used as supplements in place of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…As previously reported [18][19][20][21][22][23][24][25][26], the mesenchymal cells differentiated in culture and formed alcian blue positive chondrocyte nodules. At day 14 (figure 1a), the cultures began to show trace amounts of von Kossa positive staining.…”
Section: Characterization Of Culturessupporting
confidence: 82%
See 4 more Smart Citations
“…As previously reported [18][19][20][21][22][23][24][25][26], the mesenchymal cells differentiated in culture and formed alcian blue positive chondrocyte nodules. At day 14 (figure 1a), the cultures began to show trace amounts of von Kossa positive staining.…”
Section: Characterization Of Culturessupporting
confidence: 82%
“…Chick limb-bud mesenchymal cells plated in high-density micromass cultures differentiate to form a mineralizable matrix that resembles the growth plate in the chick [18][19][20][21][22][23][24][25][26]. Our earlier studies using 2,3-diphosphoglycerate and heparin, both non-specific inhibitors of CK2, showed inhibition of mineralization when protein phosphorylation was blocked [18].…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations